HAKIKAT RELASI MURID DAN GURU PERSPEKTIF K.H. HASYIM ASY’ARI DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALLIM - Mizan As Siddiqi; Muhamad Priyatna; Abdul Jabar Idharudin (STKIP Pesisir Selatan, 2026)
Background: Islamic education views the teacher-student relationship as a spiritual-transcendental bond, a medium for the instilling of adab, and character formation. However, the digital era has triggered an acute moral crisis, marked by the commercialization of education that alters this connection into a mechanistic transaction, stripping away the essence of character education. Objective: This study aims to deeply explore K.H. Hasyim Asy'ari’s ethical thoughts in the book Adabul 'Alim wal Muta'allim and formulate an adaptive-contextual teacher-student relationship model to address modern morality challenges. Method: The method employed is descriptive qualitative through library research with a historical-philosophical approach and textual hermeneutics. Data analysis was conducted using qualitative content analysis. Results: The study identifies five main dimensions of the teacher-student relationship according to K.H. Hasyim Asy'ari: sincerity in teaching and learning, reverence for teachers, educator exemplary, the moral-spiritual responsibility of teachers, and attaining the blessing of knowledge through adab. The integration of jurisprudence-sufism and the lillah principle distinguishes this concept from secular Western theories which tend to be positivistic-rational. Conclusion: K.H. Hasyim Asy'ari’s thought provides a solid antithesis to contemporary degradation of adab. Its contextualization demands the formation of